Stereoscopy, Brown Syndrome, and Duane Syndrome: A Literature Review - Alazi (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2022)
Stereoscopic is the ability to perceive visual objects in the depth dimension (in the third dimension). Having a stereoscopic vision is a goal to be achieved. Brown Syndrome is a rare form of strabismus in which an ocular motility disorder is characterized by restriction of the elevation of the adducted eye, whereas Duane Syndrome is a spectrum of eye motility disorders characterized by anomalous contractions of the medial and lateral rectus muscles in actual or attempted adduction of one or both eyes. Involved. Diagnosis and therapy are performed depending on the underlying condition of the disorder.